Investigating EFL learners’ knowledge of vocabulary and idiomatic expressions in a culture-based instructional environment - Ehsan Namaziandost; Mona Tavakoli; Siros Izadpanah (Universitas Syiah Kuala, 2021)
This study attempted to investigate the influences of cultural background knowledge on improving Iranian pre-intermediate EFL students’ vocabulary and idiomatic expressions. To reach this purpose, the Oxford Quick Placement Test (OQPT) was performed on 100 English as a foreign language (EFL) learners and 60 of them were selected. The selected respondents were then randomly divided into three groups: group A (Target Culture=TC), group B (Iranian Culture = IC), and group C (Culture-Free=CF). Afterwards, a vocabulary- idiomatic expressions pre-test was given to all groups. Then, the respondents of the three groups received three different treatments. Regarding the treatment, 10 texts pertinent to the customs and the culture of Iran were taught to the IC group, meanwhile, 10 texts with the new vocabulary and idiomatic expressions relevant to the target culture were taught to the TC group, and 10 culture-free texts including some new words and idiomatic expressions were trained to the CF group. After the instruction which took 10 sessions of 60 minutes each, the data were analyzed by using one-way ANOVA and paired sample t-test. The results depicted that the TC and the IC groups outflanked the CF group. This study has numerous implications for learners, teachers, and curriculum designers.